Reception of Muslims to the Ḥadīth Prohibition of Praying for Non-Muslim Spirits in a Multi-Religious Society - ., Kasman; ., Makhrus; Budiono, Arief (Journal of Ecohumanism, 2024)
Prophet Muḥammad was not allowed to pray for his mother’s spirit. Based on this ḥadīth, scholars generally prohibit Muslims from praying for non-Muslim spirits. However, not all Muslims are in line with the general views of these scholars, especially those who live in a multi-religious society. This paper aims to investigate the reception of Muslims in a multi-religious society towards the ḥadīth prohibiting praying for non-Muslim spirits. There were two substances studied here: the model of Muslim reception of the ḥadīth prohibiting praying for non-Muslim spirits, and the factors that influenced it. By using a qualitative descriptive method, we found that: first, they generally perceived it in a negotiated decoding position, which prohibits praying but does not prohibit attending prayers for non-Muslim spirits. We also found Muslims with an oppositional decoding position, which allows praying for and attending events to pray for non-Muslim spirits; and some perceived it in a dominant decoding position, which forbids praying and attending events to pray for non-Muslim spirits. Second, life experiences and beliefs may have influenced the occurrence of differences in the reception of Muslims in this multi-religious society.